HEDONIC QUALITY OF PASTEURIZED COW’S MILK WITH THE ADDITION OF SPICES - Rohmad Maulidin Jamil; Zakaria Husein Abdurrahman; Angela Nitia Nefasa (Tropical Animal Science, 2022)
This study aims to determine the effect of the addition of spices to the quality of pasteurized milk using hedonic test. The ingredients used were 7.4L of fresh cow's milk, 0.5 kg of granulated sugar, 37 g of ginger powder, 3.7 g of cinnamon powder, 37 g of turmeric powder, and aquades. The pasteurization process consist of, filtering the fresh cow's milk, then divided it into two parts. The first part is made into pasteurized milk without the addition of spices, then the second part is made into pasteurized milk with the addition of spices. If the second milk has reached a temperature of 40 °C then the spices are mixed by dissolving it in a little amount of the second milk. When the spices are dissolved, then put it into pasteurized milk to homogenize perfectly. After the temperature reaches 63°C for 30 minutes, the milk is kept until the milk temperature drops and is ready to be packaged. Pasteurized milk is then packaged in 100 mL bottles. Packaging of the first part of milk without the addition of spices are in total of 37 sample bottles and the second part of pasteurized milk with the addition of spices are in total of 37 sample bottles. This research design uses a complete randomized design of one-way pattern and 25 repetitions. Each repeat uses pasteurized milk with the same storage time and a different raw material composition. The data obtained from the hedonic test were analysis with one-way anova, to find out the comparison between pasteurized milk without spices with pasteurized milk with the addition of spices. The results showed that the panelists preferred the color, taste, texture, aftertaste of pasteurized milk without the addition of spices and the panelists preferred the aroma of pasteurized milk with the addition of spices.